Pengaruh Teknik Relaksasi Nafas Dalam terhadap Intensitas Nyeri pada Persalinan Kala I Fase Aktif di PMB Y Karawang - Imelda Diana Marsilia; Nina Tresnayanti (Universitas Baiturrahim, 2021)
Mothers who are facing the labor process will feel pain related to uterine contractions, various ways have done to reduce pain, namely by non-pharmacological techniques, including deep breathing relaxation, massage, changes in the mother's position so that labor can run safely and comfortably. This study aims to determine the effect of deep breath relaxation techniques on pain intensity in the active phase of labor. This research is a quasi-experimental design approach method pre test and post test. The sampling technique used accidental sampling as many as 28 mothers had birth in July - August BPM Y Karawang. The results of the data normality statistical test used the Shapiro-Wilk test. Data analysis using the Wilcoxon test obtained signed rank p value 0.0000 <0.05. The conclusion are that there are an effect of deep breath relaxation techniques on decreasing the pain intensity of the active phase of labor. The suggestion of this study is that deep breath relaxation techniques can be recommended as a complementary tearpie and applied to relieve pain during labor, so that labor can run smoothly